(untitled) (CIPEEX, 2025)
According to the Brazilian Institute of Geography and Statistics (IBGE), 15.8% of Brazilians are elderly, representing an increase of 56% compared to 2010. Falls in the elderly are a public health problem. The main risk factors are: female gender, older age, polypharmacy, use of psychotropic drugs, history of falls, visual impairment, environmental factors, and cognitive decline. Studies show that 69.7% of older adults who have had a fall are related to medication influences. The objective of this study was to identify the history of falls, medication use, and health status of elderly people participating in activities at UniAPI-UniEVANGÉLICA. A questionnaire was used to analyze the history of falls, self-reported health conditions, and the Beers criteria for classifying medications in use. This was a cross-sectional, descriptive field study. The sample consisted of 120 elderly individuals, 91.6% of whom were women, with a mean age of 71 years. Regarding the history of falls, 40% reported having suffered a fall in the previous 12 months, most of whom had fair or poor vision, wore glasses, and were hypertensive. Regarding medication use, 69% of fallers were classified according to Beers’ criterion 3. Finally, it was found that a large percentage of elderly people who fell had some disease that could compromise their health, in addition to visual problems and medication use, which are risk factors for falls.